Exposure to a nanoplastic-enriched diet for fourteen days increases microglial immunoreactivity in the zebrafish telencephalon - Mans, Robert A.; Kelehear, Hannah; Rotschafer, Sarah; Ganas, Clare; Uche-Moon, Brendan; Call, Gabrielle; Mauersberg, Callie C.; Toller, Justin; Diamanduros, Andrew (Frontiers in Molecular Neuroscience, 2025)
Microscopic plastic particles (micro- and nanoplastics) are an emerging environmental contaminant detected in air, soil, water, and human food supplies. Experiments using zebrafish have shown that polystyrene nanoplastics will infiltrate numerous organ systems after ingestion, including the brain, liver, muscle, and reproductive organs. Additionally, work in rodent models and cell culture has demonstrated that nanoplastics can induce inflammatory responses by microglia and alter astrocyte function. However, the responses of microglia and astrocytes in the zebrafish brain caused by daily exposures to nanoplastics have not been tested previously. In the current study, adult zebrafish were exposed to a nanoplastic-enriched diet consisting of Artemia brine shrimp containing 44 nm polystyrene spheres, and reactive gliosis by microglia and astrocytes was examined. Microglial 4C4-immunoreactive protein was elevated in the brains of zebrafish exposed to the nanoplastic-enriched diet. Levels of glial fibrillary acidic protein (GFAP) were not affected by plastic exposure. It was determined that microglial, but not astrocytic, markers were elevated in the zebrafish brain after 14-days of exposure to a nanopolystyrene-enriched diet. These findings contribute to our understanding of how a pervasive environmental contaminant, nanoplastics, may impair brain health, especially during the initial stages of nanoplastic exposure. Additionally, this is the first study using zebrafish to evaluate glial activation in the context of nanoplastic-contaminated foods.